Eltrombopag for myelodysplastic syndromes or chronic myelomonocytic leukaemia with no excess blasts and thrombocytopenia: a French multicentre retrospective real‐life study. (20th June 2021) - Comont, Thibault; Meunier, Mathieu; Cherait, Amina; Santana, Clemence; Cluzeau, Thomas; Slama, Bohrane; Laribi, Kamel; Giraud, Jean‐Thomas; Dimicoli, Sophie; Berceanu, Ana; Le Clech, Lenaïg; Cony‐Makhoul, Pascale; et al.
Summary: Despite a moderate prevalence in low‐risk myelodysplastic syndromes (MDS) and chronic myelomonocytic leukaemia (CMML), thrombocytopenia remains a risk of severe bleeding and therapeutic options are still limited. There are only a few studies with eltrombopag (ELT), a thrombopoietin receptor agonist, in those patients. In this retrospective multicentre study, ELT was used in 50 patients with MDS and 11 with CMML, with no excess of marrow blasts and platelet counts of <50 × 10 9 /l in a 'real‐life' situation. Platelet response occurred in 47 (77%) patients. The median (range) duration of response was 8 (0–69) months. None of the eight still responders who discontinued ELT had relapsed, at a median (range) of 16 (6–23) months after ELT discontinuation. Although 36% of the patients were anti‐coagulated or anti‐aggregated only 10% of patients had Grade ≥3 bleeding events. Thrombotic events were observed in six (10%) patients, who all but one had a medical history of arterial or venous thrombosis. Progression to acute myeloid leukaemia occurred in four (7%) patients. In this first 'real‐life' study, ELT was effective and generally well tolerated in patients with MDS/CMML without excess blasts.